2013
DOI: 10.1007/s10517-013-2097-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Rat Multipotent Mesenchymal Stromal Bone Marrow Cells

Abstract: We studied multipotent mesenchymal stromal cells isolated from the bone marrow of young (1 month) and old (>12 months) rats. The cell cultures derived from old rats were characterized by lower cell yield in the primary culture, lower number of doublings, and reduced colony-forming capacity of precursor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Certainly, when it comes to maintaining bone mass, age and gender differences are well recognized. Moreover, past work has suggested that differences in bone loss between genders or during aging can be correlated with the abundance and senescence of skeletal progenitors [20, 52, 53]. Associated with our data, CTGF conditional loss of function studies have reported variable impacts on bone volume associated with animal age and gender.…”
Section: Discussionsupporting
confidence: 84%
“…Certainly, when it comes to maintaining bone mass, age and gender differences are well recognized. Moreover, past work has suggested that differences in bone loss between genders or during aging can be correlated with the abundance and senescence of skeletal progenitors [20, 52, 53]. Associated with our data, CTGF conditional loss of function studies have reported variable impacts on bone volume associated with animal age and gender.…”
Section: Discussionsupporting
confidence: 84%
“…22 It was further found that BMSCs from Wistar rats aged < 1 month old had a doubling time of 26.07 § 1.81 hours and a doubling number of 3.64 § 0.19 while rats aged > 12 months old had a doubling time of 32.20 § 3.89 hours and a doubling number of 3.07 § 0.18, suggesting that the young BMSCs replicated more quickly and to a greater degree than did the old BMSCs. 23 This phenomenon was also observed in rhesus macaques where BMSCs from young monkeys had more rapid proliferation rates than those from older monkeys. 6 The above animal studies have counterparts in human tissue research.…”
Section: Donor Age Dependent Cell Senescencementioning
confidence: 72%
“…According to the current data, reduction in O 2 concentration to the tissue‐related level in cellular microenvironment (“physiologic” hypoxia) can affect the features of various tissue‐derived MSCs . Recently, we have demonstrated an increase in the proliferative activity and CFU‐F number of adipose tissue‐derived stromal cells (ASCs), while, on the contrary, the adipogenic and osteogenic differentiation decelerated . Global microarray analysis of 22 184 genes in ASCs expanded at 5% O 2 revealed the differential gene expression of 558 genes in comparison with ASCs at 20% O 2 .…”
Section: Introductionmentioning
confidence: 88%
“…14,15 Recently, we have demonstrated an increase in the proliferative activity and CFU-F number of adipose tissue-derived stromal cells (ASCs), while, on the contrary, the adipogenic and osteogenic differentiation decelerated. [16][17][18] Global microarray analysis of 22 184 genes in ASCs expanded at 5% O 2 revealed the differential gene expression of 558 genes in comparison with ASCs at 20% O 2 . Wherein, the expression of genes involved in proliferation, cell metabolism, and signaling was upregulated, while that of the ones responsible for the connective tissue matrix and cellular cytoskeleton components decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation